Messy Europe: crisis, race, and nation-state in a postcolonial world - Loftsdóttir, Kristín; Smith, Andrea L; Hipfl, Brigitte (EASA Series, 2018)
Using the economic crisis as a starting point, Messy Europe offers a critical new look at the issues of race, gender, and national understandings of self and other in contemporary Europe. It highlights and challenges historical associations of Europe with whiteness and modern civilization, and asks how these associations are re-envisioned, re-inscribed, or contested in an era characterized by crises of different kinds. This important collection provides a nuanced exploration of how racialized identities in various European regions are played out in the crisis context, and asks what work “crisis talk” does, considering how it motivates public feelings and shapes bodies, boundaries and communities.